Serum level of adiponectin and leptin in type 2 diabetic Cigarette smokers. - Al-Kadium, Tahrir E.; Hammed, Ikhlas K.; Rashid, Nada F. (Journal of the Faculty of Medicine Baghdad, 2013)
Background: Cigarette smoking is the leading avoidable cause of morbidity and mortality in the general population; however its effects on people with diabetes are even more profound. The adipocytokines  leptin and  adiponectin  play an important role in regulating glycemia, lipidemia, endothelial dysfunction, and proinflammatory mechanisms .Objective: We aimed to investigate the profile of  adiponectin and leptin in type 2 diabetic smokers and non- smokers.Patient and Methods: Ninety overweight males attending the Teaching Laboratories, Medical City were enrolled in this study, they were arranged as 30 diabetics non smoker, 30 diabetics smokers and 30 age matched apparently healthy control group, the mean age of participants was 48.3 ± 5   years.Results: Serum adiponectin and leptin level were significantly lower in the diabetics group as compared to age and BMI matched control group (7.25 ± 0.5 Vs  9.15±0.3 and7.1 ±0.6 vs.23.5±6.3 respectively), Serum   adiponectin and   leptin level were significantly lower in diabetics who were smokers compared to the non smokers (5.5 ±0.7 Vs 8.8 ±0.9; p=0.005) and ( 5.02 ±0.6 Vs 8 ± 0.9;p=0.01 respectively), Adiponectin correlate negatively with BMI and positively with age .Fasting venous blood samples were collected from all the subjects. The serum was used for analyzing Fasting Blood Glucose (FBG), Total cholesterol (TC), HDL-cholesterol (HDL-C), Triglycerides (TG).HbA1c was estimated by high performance liquid chromatography, LDL-cholesterol was calculated by Friedwald and Frederickson formula. Enzyme linked immune assay were used to measure Insulin, Adiponectin  and leptin . BMI was calculated as weight in kilograms divided by height in meters squared. Insulin resistance was calculated using HOMA-IR 1 Analysis of data was performed using the statistically package for social science (SPSS) version 17.0.Conclusion: The level of serum leptin and adiponectin were lower in diabetics who were cigarette smokers